Use of the deficit model in a shared culture of argumentation: the case of foot and mouth science - Wright, Nick; Nerlich, Brigitte (Sage, 2006)
The "deficit model" as an explanation of the public understanding of science has attracted sustained criticism. While acknowledging the limitations of the deficit model, we argue that researchers should not abandon all interest in exploring it. Our results suggest that the deficit model is an important part of a culture of argumentation shared by both scientists and members of the public, and drawn upon as explanations of the public understanding of science. We carried out discourse analysis of a focus group conducted at the height of the UK's Foot and Mouth Disease crisis. The focus of our analysis was a debate about the science behind the spread and control of the virus. The results point to the importance of the deficit model in the public understanding ofthe public understanding of science. The challenge is to look to other ways of describing the relation between science and society, while recognizing that the deficit model serves scientists, the public and others alike as a resource for political discourse.